Synthesis and Application of Novel Coal Fly Ash Supported C-Doped TiO2-SnO2 Photocatalytic Nanocomposite for the Removal of Dyes in Water - Sambakanya, S.; Nyamukamba, P.; Katwire, D.M.; Mungondori, H.H.; Mukumba, P.; Okoh, O. (Asian Journal of Chemistry, 2020)
Herein, the preparation, characterization and applications of novel carbon doped titanium dioxide and tin oxide nanocomposite supported on coal fly ash (C-TiO2-SnO2/CFA) are reported. The nanocomposite nanoparticles were successfully synthesized by a sol-gel method and calcined at 550 ºC. XRD analysis showed that SnO2 nanoparticles were polycrystalline in nature and TiO2 had both anatase and rutile phases. Diffuse reflectance spectra showed that carbon doping reduced the band gap of TiO2 from 3.19 eV to 2.78 eV. The nanoparticles′ photocatalytic activity was evaluated using methyl orange and methylene blue dyes, under both UV light and solar irradiation at different pH, pollutant concentration and photocatalyst loading. High photodegradation rates of methyl orange were achieved under visible light. The optimum loading of composite photocatalyst was 0.4 g with removal efficiencies of 97.75% for methyl orange and 99.25% for methylene blue after 3 h. High removal efficiencies were achieved for methyl orange at pH 3 and for methylene blue at pH 10.